Phytochemical Profiling and Toxicological Assessment of Ethanolic Leaf Extract of Pavetta crassipes in Wistar Rats - Omenesa, R. L.; Abba, A. M.; Umar, Z.; Kereakede, E.; Aliyu, M. T.; Muhammad, B. U. (Sahel Journal of Life Sciences FUDMA, 2025)
Toxicity studies are essential for assessing the safety of medicinal herbs. This study evaluates the phytochemical profile and toxicological assessment of ethanolic leaf extract of Pavetta crassipes in Wistar rats. Standard methods revealed the presence of alkaloids, cyanogenic glycosides, flavonoids, phenols, tannins, and terpenoids. Acute and sub-acute toxicity was assessed via oral administration of varying extract doses. During a 14-day acute toxicity trial, no mortality or observable toxicity was noted at doses of 1000, 1500, 2000 and 2500 mg/kg, indicating a median lethal dose (LD50) > 2500 mg/kg. In 28-day sub-acute tests, no significant changes (p > 0.05) were observed in body weight, relative organ weight, or in biochemical and haematological parameters compared to controls. Notably, increased extract concentrations were associated with decreased creatinine and increased granulocyte levels. These findings suggest the ethanol leaf extract is likely safe for oral use; however, further research is required to identify optimal concentrations for potential therapeutic applications in humans.